2015
DOI: 10.1080/10426914.2015.1048365
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nano-fillers on the Strength Reinforcement of Novel Hybrid Polymer Nanocomposites

Abstract: The aim of this paper is to investigate the effect of the ratio of fillers, such as multiwalled carbon nanotubes (MWCNTs) and graphene nanoplatelets (GNPs), as well as different matrix stiffnesses, on the tensile strength of epoxy/polyester material. These fillers are added to epoxy/polyester solutions in various ratios and mixed well before moulding. Experimental specimens are then made by means of the hot press process and utilizing the same curing and post-curing conditions. To investigate the effect of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…1 3 In the last decades, nanoparticles of carbon nanotubes (CNT), graphene (GR), and carbon nanodiamonds became very popular fillers for plastics for the concerns of their excellent mechanical, electrical, and thermal properties. 4 –9 Broad applications of carbon nanoparticles containing polymer composites have been proposed, which are mostly related to household, 10 automotive, 11 energy storage, 12 biomedical, 13 tissue engineering, 14 and smart materials applications. 15 The right choice of manufacturing strategy plays a crucial role in the achievement of the final properties of the produced carbon nanoparticles-filled polymer materials.…”
Section: Introductionmentioning
confidence: 99%
“…1 3 In the last decades, nanoparticles of carbon nanotubes (CNT), graphene (GR), and carbon nanodiamonds became very popular fillers for plastics for the concerns of their excellent mechanical, electrical, and thermal properties. 4 –9 Broad applications of carbon nanoparticles containing polymer composites have been proposed, which are mostly related to household, 10 automotive, 11 energy storage, 12 biomedical, 13 tissue engineering, 14 and smart materials applications. 15 The right choice of manufacturing strategy plays a crucial role in the achievement of the final properties of the produced carbon nanoparticles-filled polymer materials.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained positive results were explained by the homogeneous morphologies of the EP//UP blend and the chemical reactions between the reactive groups of EP and nanoparticles. However, Le and Huang [ 192 ] compared the effects of multiwalled carbon nanotubes (MWCNTs) and graphene nanoplatelets (GNPs) on the mechanical properties of an epoxy/unsaturated polyester mixture at different ratios. As in previous investigations, it was confirmed that a small amount of added MWCNTs (1 wt%) or GNPs (0.2 wt%) resulted in a significant increase of about 85% in the tensile strength of the epoxy/polyester blend.…”
Section: Hybrid Epoxy Nanocompositesmentioning
confidence: 99%
“…Wang et al [10] produced nanocomposite by using graphene nanoplatelets and epoxy resin. To obtain the hybrid polymer nanocomposites Le and Huang [11] stirred graphene nanoplatelets and multi-walled carbon nanotubes with epoxy/polyester solutions. According to this literature survey, few studies deal with the effects of graphene nanoplatelets reinforcement on the mechanical properties of continuous fiber-reinforced laminated composites.…”
Section: Continuousmentioning
confidence: 99%